Properties of silica nanofluid in glycerol-ethylene glycol mixture as base liquid - Akilu, S. (Asian Research Publishing Network, 2016)
Base liquid properties are critical in heat transfer due to their flexible capabilities to suit a wide range of applications. The addition of two pure miscible liquids alters thermo-physical properties, which could in turn influence the desired heating or cooling performance. A binary mixture of engineered base liquid with nanoparticle dispersions results in enhanced properties as compared to base fluid mixture. In this paper, thermophysical properties viz. viscosity, density and thermal conductivity are evaluated for silica nanofluid in glycerol/ethylene glycol mixture in 60:40 ratio for particle concentration in the range of 1.0 to 4.0 vol. and temperatures of 20°C-80°C. The experimental results showed that the properties of density and viscosity decreased whilst specific heat capacity and thermal conductivity of the nanofluid both increased with temperature. The property enhancement ratio for flow under turbulent conditions indicates heat transfer enhancements at low concentrations and high temperature for the SiO2 nanofluid. © 2006-2016 Asian Research Publishing Network (ARPN).